Field enhancement effect in reactive ion etching – a novel mechanism for plasma processing and plasma diagnostics - Bingdong Chang; Gwendoline A.E. Anand; Xiyuan Liu; Henri Jansen; Lucia Romano; Anpan Han (Materials & Design)
Field enhancement effect (FEE) is a physical phenomenon widely investigated in the context of field emitters and nanophotonic devices, where electromagnetic fields can be enhanced significantly at geometrically sharp boundaries. Here, we propose and report the FEE in the plasma sheath when geometrically sharp silicon microstructures are plasma processed by reactive ion etch (RIE). When a thin film covers the silicon structures, argon ions preferentially etch the thin films at sharp geometries due to FEE. The FEE “hotspots” are clearly visualized by adding a subsequent isotropic RIE process using SF6 chemistry. We correlated the dimensions of the hotspot profiles to the field enhancement factor (FEF). Finite element methods investigated the dependence of tip aspect ratio, the FEF, and the dimensions of hotspot profiles for hemisphere-on-cone and elliptic geometries. The critical FEF was determined to be 1000 to 2500 with Si substrate and a specified plasma condition. The knowledge gained from this study predicts FEE in plasma processing, and we apply it to fabricate nanocavities and large- area mapping electric fields for plasma diagnostics. Our study provides new insights into the plasma processing of sharp geometries, which are essential for robust chip fabrication, as the device size shrinks due to Moore’s Law and FEE in device fabrication becomes ubiquitous.